ADRENAL GLAND - Akiyev Serdarbek Panji O‘g‘li,; Jumayev Sardor Shuxrat O‘g‘li,; Ergashev Ilxom Nurulla O'gli,; Eshmuratov Sardor Eldor O'g'li, (TADQIQOTLAR, 2026)
Annotation:  anatomical,  physalogic  and  histalogic  structure  of  the  adrenal gland. Connection of the adrenal gland with the kidney.Causes of internal secretory gland penetration.A radical study of the hormones produced by the adrenal gland and their effecti e  mehaniz.  Blood supply to the adrenal gland and control through the nervous system. This is the prevention and treatment work of the sick.